Optimizing Instagram Engagement Strategies for Culinary SMEs: Evidence from the Bakpia Juwara Satoe Account - Wahyu Purnomo; Guntur Andi Pamungkas (PT. Hidayat Muda Intelektual, 2025)
Instagram has become a key digital platform for small and medium-sized enterprises (SMEs) seeking to strengthen audience engagement through visual communication. This study examines the engagement strategies implemented by Bakpia Juwara Satoe, a local culinary brand that utilizes Instagram as its primary promotional and branding medium. Using a qualitative descriptive case study approach, the research explores how content planning, visual presentation, interaction management, and credibility-building practices shape audience engagement. Data were collected through in-depth interviews with account managers, participant observation of audience interactions, and analysis of internal Instagram analytics and content archives. The findings indicate that Bakpia Juwara Satoe applies adaptive and predictive content planning supported by a consistent visual identity, attention-grabbing visual hooks, and active two-way communication in the comment section. Authentic storytelling and transparent product information further contribute to audience trust and sustained engagement. The study concludes that effective Instagram engagement for culinary SMEs does not depend solely on video-based content. Instead, strategic relevance, visual consistency, and relational communication play a decisive role in enhancing engagement outcomes. These findings contribute to social media marketing literature by highlighting alternative engagement strategies applicable to SMEs operating in competitive digital environments.